Pengembangan Perangkat Pembelajaran Fisika Berbasis Pendidikan Karakter dengan Model Problem Based Instruction - Diani, Rahma (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2015)
The unavailable of physics material learning based by the character education which conform with students’ characteristic caused the students’ competency and activity in study process was low. This research aims to develop physics material learning (syllabus, lesson plan, module, worksheet, and assessment) based by the character education with validity, practical, and effective problem based instruction model for the temperature and heat subject. This research was the development research by using 4D models. The phases are define, design, and develop. The researcher did the analysis of curriculum, analysis of concepts, and analysis of students at define phase. On design phase, the researcher designed the physics material learning. Develop phase consist of validation phase, practicality, and effectivity. After designed, the physics material learning was validated by 5 validator. At practicality phase, physics material learning tested by the students of XB MAN 1 Sungai Penuh on even semester 2012/2013. At this activity, student and teacher will be ask for their comments about the practicality of physics material learning. Effectivity of physics material learning investigated at the same time with practicality phase. At this activity, student and teacher will be ask for their comments about the effectivity of physics material learning. Effectivity also seen from the improving of student’s competency and student’s activity in study process. The result showed that physics material learning based character education with model of problem based instruction are very valid, very practical and very effective. Ketidaktersediaan materi pembelajaran fisika dengan pendidikan karakter yang sesuai dengan karakteristik siswa karena kompetensi dan kegiatan siswa dalam proses belajar termasuk rendah. Penelitian ini bertujuan untuk mengembangkan bahan ajar fisika (silabus, rencana pembelajaran, modul, lembar kerja, dan penilaian) berdasar pada pendidikan karakter dengan validitas, prktik, dan masalah efektif berdasarkan model instruksi materi suhu dan kalor. Penelitian ini merupakan penelitian pengembangan menggunakan model 4D. Tahapan tahapannya ialah; menjelaskan, desain, dan mengembangkan. Peneliti menganalisa kurikulum, menganalisa konsep, dan menganalisa siswa pada tahap tertentu. Pada tahap desain, peneliti mendesain bahan ajar fisika. Mengembangkan tahapan yang terdiri dari tahap validasi, praktikalitas, dan efektifitas. Setelah di desain, bahan ajar fisika divalidasi oleh 5 validator. Pada tahapan praktikalitas, bahan ajar fisika di uji oleh siswa kelas XB MAN 1 Sungai Penuh pada semester genap 2012/2013. Pada kegiatan ini, siswa dan guru akan ditanyakan komentarnya tentang prktikalitas pada bahan ajar fisika. Efektifitas pada bahan ajar fisika diteliti pada saat yang sama dengan tahap praktikalitas. Efektifitas juga dilihat dari meningkatnya kompetensi dan kegiatan siswa pada proses pembelajaran. Hasil menunjukkan bahwa bahan ajar fisika berdasarkan pendidikan karakter dengan instruksi Problem Based Model sangat valid, sangat praktikal dan sangat efektif.